Haglund’s deformity: Clinical outcomes of endoscopic calcaneoplasty - Rızvanoğlu, İbrahim Halil; Gönder, Nevzat; Çalışal, Emre (Acta Medica, 2024)
Objective: Haglund’s deformity is characterized by a bony prominence of the calcaneus, leads to posterior heel pain, swelling, and morning stiffness. Endoscopic calcaneoplasty is becoming increasingly popular due to its numerous advantages over conventional surgical methods. This study aims to evaluate the clinical and radiological results of patients who underwent endoscopic calcaneoplasty. Materials and Methods: A total of 17 patients were diagnosed with Haglund’s deformity and underwent endoscopic calcaneoplasty surgery in our clinic between June 2019 and January 2023 were included in this retrospective study. Pre-operative and post-operative parameters of patients with 6 months or more of follow-up were compared. The VAS was used for pain assessment, the AOFAS score for functional outcomes, and the length of bone deformity for radiological assessment. Results: Significant pain resolution was observed at the final follow-up compared to the preoperative period. The mean VAS score decreased from 6.77±1.3 pre-operatively to 1.62±1.12 post-operatively (p<0.001). The AOFAS score showed a significant increase from 61.23±7.7 preoperatively to 92.46±6.04 postoperatively (p<0.001). Bony hump length decreased significantly from 4.12±1.14 preoperatively to -2.29±1.56 postoperatively (p<0.001). Conclusion: Endoscopic calcaneoplasty is a reliable method in Haglund’s deformity, that provides rapid recovery, early return to daily activities and sports, and a low complication rate.